Indonesia, Debt Burden and Development in the Era of Joko Widodo: A Critical Note - Herdi Sahrasad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
Indonesia's economy under Jokowi confronts severe corruption and an escalating debt burden. The populace confronts a deterioration in economic growth and purchasing capacity. Indonesia faces the risk of becoming a